Translating CO2 variability in a plant growth system into plant dynamics - Ahn, Tae In; JUNG, JE HYEONG; Kim, Hyoung Seok; Lee, Ju Young (Nature Publishing Group, 2022)
Plant growth occurs owing to the continuous interactions between environmental and genetic factors, and the analysis of plant growth provides crucial information on plant responses. Recent agronomic and analytical methodologies for plant growth require various channels for capturing broader and more dynamic plant traits. In this study, we provide a method of non-invasive growth analyses by translating CO2 variability around a plant. We hypothesized that the cumulative coefficient of variation (CCV) of plant-driven ambient CO2 variation in a plant growth system could yield a numerical indicator that is connected to the plant growth dynamics. Using the system outside-plant growth system-plant coupled dynamic model, we found that the CCV could translate dynamic plant growth under environmental and biophysical constraints. Furthermore, we experimentally demonstrated the application of CCV by using non-airtight growth chamber systems. Our findings may enrich plant growth information channels and assist growers or researchers to analyze plant growth comprehensively.